The influence of P. fluorescens cell morphology on the lytic performance and production of phage ϕIBB-PF7A - Sillankorva, Sanna (2011)
This study aims at assessing the influence of Pseudomonas fluorescence cell morphology on the effectiveness and production of the lytic bacteriophage /IBBPF7A. P. fluorescens were cultured as rods or as elongated cells by varying the temperature and rotary agitation conditions. Cells presented rod shape when grown at temperatures up to 25C and also at 30C under static conditions, and elongated morphology only at 30C when cultures were grown under agitation. Elongated cells were 0.4 up to 27.9 lm longer than rod cells. Rod-shaped hosts were best infected by phages at 25C which resulted in an 82% cell density reduction. Phage infection of elongated cells was successful, and the cell density reductions achieved was statistically similar (P[0.05) to those obtained at the optimum growth temperature of P. fluorescens. Phage burst size varied with the cell growth conditions and was approximately 58 and 153 PFU per infected rod and elongated cells, grown at 160 rpm, at 25C (the optimal temperature) and 30C, respectively. Phage adsorption was faster to elongated cells, most likely due to the longer length of the host. The surface composition of rod and elongated cells is similar in terms of outer membrane proteins and lipopolysaccharide profiles. The results of this study suggest that the change of rod cells to an elongated morphology does not prevent cells from being attacked by phages and also does not impair the phage infection.